2016
DOI: 10.1097/md.0000000000003657
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Changes in Biochemical Markers for Skeletal Muscles, Hepatic Metabolism, and Renal Function after Three Types of Long-distance Running

Abstract: The purpose of this study is to compare changes in biochemical markers for the skeletal muscles, hepatic metabolism, and renal function based on extreme long-distance running.Among healthy amateur endurance athletes who participated in a marathon, 100 km-, or 308 km ultramarathon, 15 athletes with similar physical and demographic characteristics were chosen to be the subjects in this study, upon completion of each course. The subjects’ blood was collected before and after the course to identify biochemical mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
73
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 39 publications
7
73
0
5
Order By: Relevance
“…The abscissa represents different experimental groups, the ordinate represents the comparison of the metabolites among different groups, and the color blocks at different positions represent the relative expression of the corresponding metabolites. b Bubble plot displays the increasing impact of the enrichment analysis of metabolic pathways, with key bubbles reflecting that the metabolic pathways were significantly altered by marathon In the aspect of evaluating exercise fatigue, Shin demonstrated that the serum urea, CK and other biochemical indicators of the athletes who completed marathon match, were all significantly elevated [21]. Moreover, the athletes subjectively felt fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The abscissa represents different experimental groups, the ordinate represents the comparison of the metabolites among different groups, and the color blocks at different positions represent the relative expression of the corresponding metabolites. b Bubble plot displays the increasing impact of the enrichment analysis of metabolic pathways, with key bubbles reflecting that the metabolic pathways were significantly altered by marathon In the aspect of evaluating exercise fatigue, Shin demonstrated that the serum urea, CK and other biochemical indicators of the athletes who completed marathon match, were all significantly elevated [21]. Moreover, the athletes subjectively felt fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Strenuous exercise with eccentric muscle contractions may be attributed to muscle fatigue due to muscle membrane damage along with increase intermuscular enzymes and biomarkers [2,9,31,32,47]. In our study, we concluded that 25(OH)D production after vitamin D supplementation has a significant effect on selected biomarkers of skeletal muscle damage and post-exercise proinflammatory cytokine levels.…”
Section: Discussionmentioning
confidence: 58%
“…In previous studies on the assessment of muscle dysfunction, the conventional biomarkers (e.g., Tn, CK, myoglobin, LDH) have been analyzed [30,31]. These markers had different release times and different times of reaching maximal concentrations [9,11,32]. It has been hypothesized that exercise-induced lower muscle biomarker secretion may depend on increased serum 25(OH)D levels and these vitamin levels might be used for early detection of greater muscle resistance to eccentric-induced muscle fatigue [31].…”
Section: Introductionmentioning
confidence: 99%
“…CK catalyzes ATP dependent phosphorylation of creatine, and LDH is involved in the metabolism of pyruvate in skeletal muscle [49,50]. CK and LDH are reported to serve as markers of acute or chronic muscular damage and cell necrosis [51,52]. Additionally, activation of CK and LDH may increase symptoms such as pain, fatigue, and a decline in muscular strength during high-intensity, long-distance exercise due to damaged skeletal muscles [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…CK and LDH are reported to serve as markers of acute or chronic muscular damage and cell necrosis [51,52]. Additionally, activation of CK and LDH may increase symptoms such as pain, fatigue, and a decline in muscular strength during high-intensity, long-distance exercise due to damaged skeletal muscles [51,52]. Recently, in an animal study, SC was shown to effectively delay CK and LDH increases after acute exercise [13], but another animal study did not shown in this effect [53].…”
Section: Discussionmentioning
confidence: 99%